African Diplomacy in Resolving International Conflicts: An Analytical Study of the Legal Framework and Peaceful Mechanisms (Al-Farooq Journal of Sciences, 2026)
This research examines African diplomacy in the settlement of international disputes by analyzing its legal framework and peaceful mechanisms. It shows that African diplomacy is based on international and African legal instruments, including the United Nations Charter, the Charter of the Organization of African Unity, the Constitutive Act of the African Union, and the Protocol establishing the African Peace and Security Council، The study highlights negotiation, mediation, good offices, inquiry, and conciliation as key peaceful tools. It concludes that the effectiveness of African diplomacy depends on political will, institutional coordination, and the follow-up of implemented agreements.
Keywords: African diplomacy, dispute settlement, African Union, mediation, peaceful mechanisms.